When is a Choice not a Choice? ‘Sham Offers’ and the Asymmetry of Adolescent Consent and Refusal - Manson, Neil C. (Bioethics, 2017)
In some jurisdictions there is a puzzling asymmetry between consent and refusal, where, for some kinds of treatment, the adolescent patient has the power to permit her own treatment but her refusal does not have the same kind of normative significance as refusal of treatment by a competent adult. In this journal I recently offered a clarification and defence of this asymmetry in terms of a paternalistic justification of the sharing of normative powers between adolescents and other parties. Lawlor (2016) offers a number of objections to this account. Three of his objections can be dealt with quickly. But one of them is much more challenging: the asymmetry of consent and refusal entails a practice of making sham offers (offers that purport to be responsive to the patient's choices, but which, in fact, are not). They do not really offer a choice at all. Genuine offers seem to require a commitment to be symmetrically responsive to whatever decision outcome is reached by the recipient of the offer. When we reflect upon the way that offers can be made in complex social contexts, where different parties have a ‘say’ in what ought to be done, the symmetry of responsiveness need not apply. Offers can be genuine, without being symmetrically responsive. Contrary to the seemingly plausible objection, the asymmetry of consent and refusal does not entail sham offers, or the offer of ‘sham choices’.